Bargaining in international trade under exchange rate uncertainty - Shabtai Donnenfeld; Itzhak Zilcha (Universität Konstanz, Sonderforschungsbereich 178 - Internationalisierung der Wirtschaft, 1994)
This paper studies the implications of various contracting alternatives between exporting and importing firms on the value of production and international transactions. Since contracts are usually determined when exchange rate is uncertain, we show that under some conditions renegotiating these initial trade contracts can be beneficial to both parties. In such Nash-type bargaining solutions the initial contract is the disagreement point. It is shown that when renegotiation is possible, the firm produces more and the expected export is higher. Our results have some implications to well-known results concerning vertical integration as well.
Keywords: 330